(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the social and psychological importance of the process of preparing girls for family life, the need to reconsider national traditions and gender stereotypes, ways to increase efficiency through the formation of family life skills, expanding the topic of the family in educational programs, and the use of innovative technologies. The article also reveals the role that girls play in ensuring the stability of society in the future by becoming personally and socially responsible family members.